Yap5 Competes With Hap4 for the Regulation of Iron Homeostasis Genes in the Human Pathogen Candida glabrata - Delaveau, Thierry; Thiébaut, Antonin; Benchouaia, Médine; Merhej, Jawad; Devaux, Frédéric (Frontiers in Cellular and Infection Microbiology, 2021)
The CCAAT-binding complex (CBC) is a conserved heterotrimeric transcription factor which, in fungi, requires additional regulatory subunits to act on transcription. In the pathogenic yeast Candida glabrata, CBC has a dual role. Together with the Hap4 regulatory subunit, it activates the expression of genes involved in respiration upon growth with non-fermentable carbon sources, while its association with the Yap5 regulatory subunit is required for the activation of iron tolerance genes in response to iron excess. In the present work, we investigated further the interplay between CBC, Hap4 and Yap5. We showed that Yap5 regulation requires a specific Yap Response Element in the promoter of its target gene GRX4 and that the presence of Yap5 considerably strengthens the binding of CBC to the promoters of iron tolerance genes. Chromatin immunoprecipitation (ChIP) and transcriptome experiments showed that Hap4 can also bind these promoters but has no impact on the expression of those genes when Yap5 is present. In the absence of Yap5 however, GRX4 is constitutively regulated by Hap4, similarly to the genes involved in respiration. Our results suggest that the distinction between the two types of CBC targets in C. glabrata is mainly due to the dependency of Yap5 for very specific DNA sequences and to the competition between Hap4 and Yap5 at the promoter of the iron tolerance genes.